2012
DOI: 10.1590/s0103-84782012001000005
|View full text |Cite
|
Sign up to set email alerts
|

Fontes e doses de nitrogênio para mamoneira de porte baixo no sistema plantio direto

Abstract: IVFontes e doses de nitrogênio para mamoneira de porte baixo no sistema plantio direto Nitrogen fertilizers and rates in castor bean hybrids under no-till system

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…equal to 0.6 dS m -1 ; and 6.3 to 11.2 g kg -1 when irrigated with higher water salinity (4.6 dS m -1 ) consisting of increase per unit increase of ECw 14.2 and 11.0% for TN and TP, respectively. These trends are similar to Moro et al (2012) when evaluating different sources of nitrogen in fertilizers in the cultivation of hybrid Savannah; the authors found phosphorus content in shoots between 2.7 to 3.3 g kg -1 . Severino et al (2008) in a study with BRS Northeastern observed phosphorus content in plant tissue ranging from 2.9 to 10.6g kg -1 , using different substrates.…”
Section: Results Anddiscussionsupporting
confidence: 72%
See 1 more Smart Citation
“…equal to 0.6 dS m -1 ; and 6.3 to 11.2 g kg -1 when irrigated with higher water salinity (4.6 dS m -1 ) consisting of increase per unit increase of ECw 14.2 and 11.0% for TN and TP, respectively. These trends are similar to Moro et al (2012) when evaluating different sources of nitrogen in fertilizers in the cultivation of hybrid Savannah; the authors found phosphorus content in shoots between 2.7 to 3.3 g kg -1 . Severino et al (2008) in a study with BRS Northeastern observed phosphorus content in plant tissue ranging from 2.9 to 10.6g kg -1 , using different substrates.…”
Section: Results Anddiscussionsupporting
confidence: 72%
“…From this point on, increases to the highest level saline were observed, where TK obtained in the leaves was 45.3 g kg -1 . Crusciol et al (2012) evaluated the extraction and exportation of macronutrients by Savannah castor hybrid and they found at 97 days after emergence, 9.9 g kg -1 of K during the 2005/2006 season and 10.6 g kg -1 of K in the 2006 harvest at 100 days after emergence. The reduction in potassium absorption is possibly related to the increased concentration of sodium in root, through inhibiting the absorption of potassium due to the competitive relationship between these cations (Kawasaki et al, 1983); as well as it is associated with competition for uptake at the level of membrane sites (Bloom & Epstein, 2006).…”
Section: Results Anddiscussionmentioning
confidence: 99%